'The most popular star-tutor of English': discursive construction of tutor identities in shadow education. Issue 1 (2nd January 2020) - Yung, Kevin Wai Ho; Yuan, Rui
ABSTRACT: Private tutoring has become a widespread phenomenon worldwide, partly due to the global trend of marketisation and commodification of education. Informed by a discursive view of identity and through multimodal discourse analysis, this study aims to unveil part of the shadow education discourse by investigating the identities of 41 English language tutors portrayed in their biographies on the websites of six leading tutorial schools in Hong Kong. The findings suggest that the tutors project identities as (1) an authoritative exam expert, (2) a popular star, and (3) a well-qualified English language teacher. These multiple identities overlap and collectively create an 'exam expert-star-teacher' hybrid identity. The study sheds light on how implicit values and beliefs about shadow education are created and manifested in educational and social discourses, particularly when biography in tutorial advertisements is a prevailing commercial genre with promotional purposes.